A Ready-to-Use Antifungal Starter Culture Improves the Shelf Life of Packaged Bread - Gerez, Carla Luciana (2010)
Fungal spoilage is the main cause of economic loss in the baking industry. In this study, we developed a ready-to-use biopreserver (slurry [SL]) for nonsliced packed bread by using selected antifungal lactic acid bacteria (LAB) and low-cost ingredients that are compatible with the food matrix. Four LAB strains (Lactobacillus brevis CRL 772, L. brevis CRL 796, L. plantarum CRL 778, and L. reuteri CRL 1100) tested in bread preservation were able to inhibit Pénicillium sp. growth and lengthen shelf life twofold with respect to breads prepared using only Saccharomyces cerevisiae (2 days shelf life). The best biopreservation effect (5 days shelf life) was obtained with 40% antifungal slurry SL778 containing L. plantarum CRL 778; this was as effective as 0.2% calcium propionate (PCa). The antifungal effect of SL778 was related to the synthesis of acetic and phenyllactic acid as well as lactic acid, which was produced at a high concentration (31.2 mmol/kg) and lowered the pH of the dough, favoring the undissociated fraction of the organic acids. The combination of the starter SL778 with 0.4% PCa extended the shelf life of packaged bread to 24 days, 2.6-fold longer than breads prepared with only 0.4% PCa.